Fifteen-year experience with carotid artery stenting: (from the carotid artery stenting-registry of the Arbeitsgemeinschaft Leitende Kardiologische Krankenhausärzte) - Werner, Nicolas; Zeymer, Uwe; Hochadel, Matthias; Hauptmann, Karl Eugen; Jung, Jens; Janicke, Ilse; Haase, Hartwick; Leschke, Matthias; Mudra, Harald; Zahn, Ralf (The American journal of cardiology, 2015)
To date only sparse data are available on trends and changes in indications, patient's characteristics, and clinical outcome of patients undergoing carotid artery stenting (CAS) in clinical practice. From February 1996 to December 2010, 6,116 CAS procedures were performed in 5,976 patients at 36 hospitals within the prospective, multicenter CAS registry of the Arbeitsgemeinschaft Leitende Kardiologische Krankenhausärzte. Median age of patients was 71 years, 71.6% were men; a symptomatic stenosis was treated in 50.3% and an embolic protection device (EPD) was used in 82.5% of the patients. The overall hospital mortality or stroke rate was 3.1%. Stroke or in-hospital death occurred in 4.0% in symptomatic patients and in 2.2% in asymptomatic patients. In a logistic regression model, independent predictors of in-hospital death or stroke were heart failure (odds ratio [OR] 2.03, 95% confidence interval [CI] 1.22 to 3.36, p = 0.006), symptomatic stenosis (OR 1.52, 95% CI 1.05 to 2.18, p = 0.03), and age (OR per 10 years 1.46, 95% CI 1.17 to 1.81, p <0.001). The use of an EPD was significantly associated with a lower rate of death or stroke in the registry (OR 0.45, 95% CI 0.26 to 0.78, p = 0.004). From 1996 to 2010, mean age of patients increased by 4.1 years (p <0.001), the proportion of male patients decreased from 82.4% to 70.2% (p = 0.07), the proportion of symptomatic stenoses decreased (84.6% to 24.7%, p <0.001), and the use of EPDs increased from 1.4% to 97.2% (p <0.001). Comparing 2 periods from 1996 to 2003 and 2004 to 2010, a numeric decrease in the in-hospital stroke or death rate was seen in symptomatic (4.7% vs 3.5%, p = 0.11), and in asymptomatic patients (2.9% vs 2.1%, p = 0.27) undergoing CAS, which did not reach statistical significance. In conclusion, the proportion of symptomatic carotid artery stenoses decreased significantly; EPDs established as a standard tool and a numeric decrease of in-hospital stroke or death was seen in asymptomatic and symptomatic patients undergoing CAS in clinical practice over the last 15 years.